The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1364/oe.26.023854
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-phonon-polariton modes and field enhancement in graphene-coated hexagon boron nitride nanowire pairs

Abstract: Both plasmon-phonon-polariton (SPP-PHP) modes and phonon-polariton (PHP) modes supported in graphene-coated hexagon boron nitride (h-BN) single nanowire are presented. The field distributions of the lowest 5 order modes of SPP-PHP modes supported in graphene-coated hexagon boron nitride nanowire pairs (SPP-PHP-GHNP) and the lowest 5 order modes of PHP modes supported in graphene-coated hexagon boron nitride nanowire pairs (GHNP) are also demonstrated and analyzed, respectively. The results of numerical calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Our results for FOM and the propagation length at the frequency of 45 THz is a significant enhancement, compared to the previous works [104][105][106][107]. For instance, in [104], a quality factor of 33 and a propagation length of 3.2 ฮผm are reported for propagating plasmons on a fabricated graphene-based structure.…”
Section: The Upper Reststrahlen Bandcontrasting
confidence: 40%
See 1 more Smart Citation
“…Our results for FOM and the propagation length at the frequency of 45 THz is a significant enhancement, compared to the previous works [104][105][106][107]. For instance, in [104], a quality factor of 33 and a propagation length of 3.2 ฮผm are reported for propagating plasmons on a fabricated graphene-based structure.…”
Section: The Upper Reststrahlen Bandcontrasting
confidence: 40%
“…The authors in [105] have reported the FOM of 25 in a combined graphene-hBN structure. In [106], a FOM of 45 is achieved for the first mode of graphenecoated hBN nanowires at the frequency of 44.8 THz.…”
Section: The Upper Reststrahlen Bandmentioning
confidence: 99%
“…A high value of FOM=190 is observable for ๐œ‡๐œ‡ ๐‘๐‘ = 0.85 ๐‘’๐‘’๐‘’๐‘’ at the frequency of 48.3 THz. Compared to the previous articles [90][91][92][93], our achieved FOM shows a remarkable increment. In [90], a fabricated graphene-based waveguide is investigated with a reported FOM of 33.…”
Section: Resultsmentioning
confidence: 50%
“…In [90], a fabricated graphene-based waveguide is investigated with a reported FOM of 33. In [91], a quality factor of 25 is obtained for a hybrid graphene-hBN heterostructure and the authors in [92] have reported FOM=45 for their graphene-based nano-wire. One of the important layers in our proposed device in which its parameters can change the performance is the middle substrate, which is primarily supposed to be a SiO 2 layer with a thickness of ๐‘‘๐‘‘ = 20๐‘๐‘๐‘š๐‘š.…”
Section: Resultsmentioning
confidence: 99%
“…On this basis, parallel SPWs can be constructed. [27][28][29] The nested surface plasmon waveguide coated with graphene is a research hotspot. In 2015, Yang et al designed a circular dielectric nanowire waveguide coated with two layers of graphene, [13] which can be regarded as a coaxial waveguide formed by embedding one graphene-coated dielectric nanowire into the axis of the other.…”
Section: Introductionmentioning
confidence: 99%